2023
DOI: 10.1002/cam4.5623
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation biomarkers accurately detect esophageal cancer prior and post neoadjuvant chemoradiation

Abstract: Background Esophageal cancer (ECa) is associated with high mortality, mostly due to late diagnosis, precluding curativeintent surgery. Hence, neoadjuvant chemoradiation (ChRT) is recommended in most patients regardless of histological subtype. A proportion of these patients, however, achieve complete disease remission and might be spared of radical surgery. The lack of reliable, minimally invasive biomarkers able to detect post‐ChRT disease persistence is, nonetheless, a major drawback. We have previously show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…There is limited information about the significance of DNA hypermethylation of the remaining biomarkers. Recent studies showed that the differential expression and DNA methylation pattern of these genes may be used as diagnostic and prognostic biomarkers for different types of cancer, e.g., breast cancer (NRIP3 [44], MIR129-2 [45,46]), hepatocellular carcinoma (SOX8 [47]), oesophageal cancer (MIR129-2 [48]), lung cancer (MIR129-2 [49]), and colorectal cancer (MIR129-2 [50,51]). Interestingly, the SOX gene family is generally discussed as having oncogenic properties and SOX overexpression can be associated with poor prognosis [52].…”
Section: Discussionmentioning
confidence: 99%
“…There is limited information about the significance of DNA hypermethylation of the remaining biomarkers. Recent studies showed that the differential expression and DNA methylation pattern of these genes may be used as diagnostic and prognostic biomarkers for different types of cancer, e.g., breast cancer (NRIP3 [44], MIR129-2 [45,46]), hepatocellular carcinoma (SOX8 [47]), oesophageal cancer (MIR129-2 [48]), lung cancer (MIR129-2 [49]), and colorectal cancer (MIR129-2 [50,51]). Interestingly, the SOX gene family is generally discussed as having oncogenic properties and SOX overexpression can be associated with poor prognosis [52].…”
Section: Discussionmentioning
confidence: 99%